Influence of osteopenia in autogenous bone graft healing with or without expanded polytetrafluoroethylene membranes: Histologic and histomorphometric study in rats - Nascimento, Rodrigo Dias [UNESP]; Cardoso, Paula Elaine [UNESP]; De Marco, Andréa C.; De Lima, Luiz Antonio Pugliesi Alves; Jardini, Maria Aparecida Neves [UNESP] (My University, 2009)
Purpose: The aim of this study was to quantitatively evaluate and qualitatively describe autogenous bone graft healing with or without an expanded polytetrafluoroethylene (e-PTFE) membrane in ovariectomized rats. Materials and Methods: Eighty Wistar rats, weighing approximately 300 g each, were used. A graft was obtained from the parietal bone and fixed to the sidewall of each animal’s left mandibular ramus. The animals were randomly divided into four experimental groups (n = 20 in each group): group 1, sham operated and autogenous bone graft only; group 2, sham operated and autogenous bone graft covered by e-PTFE membrane; group 3, ovariectomized (OVX) and autogenous bone graft only; group 4, OVX and autogenous bone graft covered by e-PTFE membrane. The animals were sacrificed at five different time points: immediately after grafting or at 7, 21, 45, or 60 days after grafting. Histologic examination and morphometric measurement of the sections were performed, and values were submitted to statistical analyses. Results: Both groups (sham and OVX) experienced loss of the original graft volume when it was not covered by the membrane, whereas use of the membrane resulted in additional bone formation beyond the edges of the graft and under the membrane. Histologic analysis showed integration of the grafts in all animals, although a larger number of marrow spaces was found in OVX groups. Conclusions: Association of bone graft with an e-PTFE membrane resulted in maintenance of its original volume as well as formation of new bone that filled the space under the membrane. Osteopenia did not influence bone graft repair, regardless of whether or not it was associated with e-PTFE membrane, but descriptive histologic analysis showed larger numbers of marrow spaces in the bone graft and receptor bed and formation of new bone in the OVX animals. © 2009 by Quintessence Publishing Co Inc.
Keywords: Bone regeneration; Bone transplantation; Metabolic bone diseases